Availability of eye health interventions in basic schools in a Ghanaian municipality - Adzaho, Christopher Senyo; Appiah-Brempong, Emmanuel; Acheampong, Princess Ruhama; Ekutor, Ernest (Frontiers in Public Health, 2024)
IntroductionGlobally, 19 to 22 million children are visually impaired. A huge number of children therefore will not be able to learn effectively even if the best educational institutions are made available to them. This ultimately leaves a potential negative effect on their quality of life, educational opportunities and livelihoods. School health programs (SHPs) present a unique opportunity to provide comprehensive eye health services to children. This study assessed the availability of School Eye Health Programs (SEHPs) in a municipality in Ghana.Design and methodsIn a cross-sectional study, semi-structured questionnaires and interview guides were used to collect data from 60 head teachers, 17 school health coordinators, and 7 key health workers.ResultsNo school in the municipality had a comprehensive SEHP being implemented. However, over 60% of schools had at some point introduced at least one component of SEHP, mainly Vitamin A supplementation and vision screening. Community and Public Health Nurses are the commonly used human resource for such programs. There were no available guidelines for program implementation and no systems in place for ensuring follow-up visits and provision of spectacles to those with refractive errors. Key barriers identified included the lack of financial resources and adequately trained personnel.ConclusionComprehensive school eye health programs are unavailable in the study area and there is an urgent need for their implementation to avert the potential adverse effects of vision impairment on the education of children.